About The History And Trends Of Population Migration Processes In Uzbekistan - Gapporov Azimbek Nazarovich (Peerian Journals Publishing, 2025)
The article analyzes the periodic territorial movement of the population of the Republic of Uzbekistan, studies the causes of internal and external migration movements in different years. It is known that in certain periods of the economic and political life of the country, various processes and events occurred, the impact of which on migration processes was significant. In particular, population migration is also associated with changes in the distribution of the population across the country and changes in the natural movement of the population. The periodic migration movements analyzed in the article are key factors in the development of the population and territorial distribution
Keywords: Migration; Population Movement; Settlements